2006
DOI: 10.1111/j.1532-950x.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of Two Crimp Clamp Systems for Extracapsular Stabilization of the Cranial Cruciate Ligament‐Deficient Canine Stifle

Abstract: Objective-To compare the mechanical properties and interoperator variabilities of 2 crimp clamp systems for extracapsular, fabello-tibial, nylon loop stabilization of the cranial cruciate ligamentdeficient stifle in dogs. Study Design-In vitro mechanical testing. Methods-Three operators with different grip strengths each secured 20 standardized nylon loops using stainless-steel crimp clamps: 10 using a Veterinary Instrumentation system (45 kg [100 lb] test nylon leader line, 12 mm crimp clamps) and 10 using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 16 publications
3
38
0
1
Order By: Relevance
“…Whilst implant failure is potentially a disadvantage of the use of MNL in median sternotomy closure, the loads applied in this study were substantially higher than the estimated physiological loads, therefore it is concluded that plastic deformation with subsequent irreversible construct failure was unlikely to occur for either construct at physiological loads. The mode of failure of MNL demonstrated in this study is consistent with other mechanical studies investigating nylon leader constructs for stabilisation of the CCL‐deficient stifle (Moores et al , Vianna & Roe , Cabano et al ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whilst implant failure is potentially a disadvantage of the use of MNL in median sternotomy closure, the loads applied in this study were substantially higher than the estimated physiological loads, therefore it is concluded that plastic deformation with subsequent irreversible construct failure was unlikely to occur for either construct at physiological loads. The mode of failure of MNL demonstrated in this study is consistent with other mechanical studies investigating nylon leader constructs for stabilisation of the CCL‐deficient stifle (Moores et al , Vianna & Roe , Cabano et al ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition significantly less strength and elongation were demonstrated in MNL that was crimped compared to knotted (Sicard et al ). The reason for these discrepancies may be a result of differences in operator grip strength, knotting ability and methodology (Moores et al ). The Securos crimp clamp was used as loops secured with this system were found to be significantly stronger and stiffer than the Veterinary Instrumentation system (Moores et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the suture material is secured with multiple knots, but recent work suggests that using a specific metal crimp system provides a stiffer construct. 45,46 Additional stabilization techniques include: in 1971, Pearson published a report in which tibial translation was stabilized by multiple imbricating Lembert sutures in the joint capsule and muscles lateral to the joint. 47 Hohn introduced a posterolateral capsulorrhaphy in 1975, in which the caudolateral joint capsule is imbricated in addition to advancing the musculature from the medial and lateral stifle up to the patellar ligament to prevent tibial translation and internal rotation.…”
Section: Veterinary Literaturementioning
confidence: 99%
“…In contrast Burgess et al (2010) stated that 80 lb crimped loops were significantly weaker than knotted loops and two other studies (Peycke et al 2002;Roe et al 2008) which evaluated 80 lb MNL found that crimped loops were significantly stronger than knotted MNL. The reason for these discrepancies results might lie in differences in operator grip strength, knotting ability or differences in methodology (Moores et al 2006). We recorded a significant difference between the three operators, which might affect grip strength, but all three operators are active surgeons familiar with the use of crimping tools.…”
Section: Discussionmentioning
confidence: 92%